Disruption of largest subunit RNA polymerase II genes in Trypanosoma brucei. - Chung, H M (1993)
Two types of largest subunit RNA polymerase II (pol II) genes (pol IIA and pol IIB), differing in 3 amino acid substitutions, are encoded in the Trypanosoma brucei (stock 427-60) genome. As a result, the alpha-amanitin-resistant transcription of the procyclic acidic repetitive protein (PARP) and variant surface glycoprotein (VSG) genes was proposed to involve a modified, alpha-amanitin-resistant form of the largest subunit of pol II. Alternatively, pol I could transcribe the PARP and VSG genes. To discriminate between these two models, we deleted the N-terminal domain (about one-third of the polypeptide), which encodes the amino acid substitutions which discriminated the pol IIA and pol IIB genes, at both pol IIB alleles. The pol IIB- trypanosomes still transcribe the PARP genes and the VSG gene promoter region in insect-form trypanosomes by alpha-amanitin-resistant RNA polymerases, while control housekeeping genes are transcribed in an alpha-amanitin-sensitive manner, presumably by pol IIA. We conclude that the alpha-amanitin-resistant transcription of protein coding genes in T. brucei is not mediated by a diverged form of the largest subunit of pol II and that the presence of both the pol IIA and pol IIB genes is not essential for trypanosome viability. This conclusion was further supported by the finding that individual trypanosome variants exhibited allelic heterogeneity for the previously identified amino acid substitutions and that various permutations of the polymorphic amino acids generate at least four different types of largest subunit pol II genes. The expression of the PARP genes and the VSG gene promoter region by alpha-amanitin-resistant RNA polymerases in the pol IIB- trypanosomes provides evidence for transcription of these genes by pol I.